Lampu LED bertenaga baterai akumulator untuk pencahayaan usaha dagang Mikro-Kecil di Desa Indah Karya, Kecamatan Tapung, Kabupaten Kampar, Provinsi Riau - Budhi Anto; Dahliyusmanto Dahliyusmanto; Eddy Hamdani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The government policy to convert the use of kerosene to LPG has created kerosene to become precious and rare good in the market. This condition has caused many difficulties among the micro-small moving merchants that depend on kerosene lamps for lighting their wagons at night. Thus, the solution must be carried out to ensure their business sustainability. This article reports our community services program to supply and install battery-powered LED lamps with battery chargers for moving culinary merchants in Indah Karya village, Tapung District, Kampar Regency, to provide them with more efficient and effective lighting technology. Our analysis shows that the application of battery-powered LED lamps has significantly reduced merchants' operational costs and provided more accessibility to power the lamps. We have chosen one moving merchant that sells daily needs as our partner. The LED lamps, the power inverter, and the VRLA battery are installed and wired on our partner's wagon. We have evaluated the impact of this new lighting technology on our partner's business. Based on the evaluation, our partner has experienced a substantial operational cost reduction and easy access to power his wagon's lighting.